Establishing the Signal above the Noise: Accounting for an Environmental Background in the Detection and Quantification of Salmonid Environmental DNA - Morgan D. Hocking; Jeffrey C. MacAdams; Michael J. Allison; Lauren C. Bergman; Robert Sneiderman; Ben F. Koop; Brian M. Starzomski; Mary L. Lesperance; Caren C. Helbing (Fishes, 2022)
A current challenge for environmental DNA (eDNA) applications is how to account for an environmental (or false-positive) background in surveys. We performed two controlled experiments in the Goldstream Hatchery in British Columbia using a validated coho salmon (Oncorhynchus kisutch) eDNA assay (eONKI4). In the density experiment at high copy number, eDNA in 2 L water samples was measured from four 10 kL tanks containing 1 to 65 juvenile coho salmon. At these densities, we obtained a strong positive 1:1 relationship between predicted copy number/L and coho salmon biomass (g/L). The dilution experiment simulated a situation where fish leave a pool environment, and water from upstream continues to flow through at rates of 141–159 L/min. Here, three coho salmon were placed in four 10 kL tanks, removed after nine days, and the amount of remaining eDNA was measured at times coinciding with dilutions of 20, 40, 80, 160, and 1000 kL. The dilution experiment demonstrates a novel method using Binomial–Poisson distributions to detect target species eDNA at low copy number in the presence of an environmental background. This includes determination of the limit of blank with background (LOB-B) with a controlled false positive rate, and limit of detection with background (LOD-B) with a controlled false negative rate, which provides a statistically robust “Detect” or “No Detect” assessment for eDNA surveys.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nearshore fish community responses to large scale dam removal: implications for watershed restoration and fish management - J. Anne Shaffer; Francis Juanes; Thomas P. Quinn; Dave Parks; Tara McBride; James Michel; Cayla Naumann; Morgan Hocking; Chris Byrnes (Aquatic Sciences, 2017)

Salmon nutrients are associated with the phylogenetic dispersion of riparian flowering‐plant assemblages - Leslie A. Hurteau; Arne Ø. Mooers; John D. Reynolds; Morgan D. Hocking (Ecology, 2016)
A signature of nonrandom phylogenetic community structure has been interpreted as indicating community assembly processes. Significant clustering within the phylogenetic structure of a community can be caused by habitat filtering due to low nutrient availability. Nutrient limitation in temperate Pacific coastal rainforests can be alleviated to some extent by marine nutrient subsidies introduced by migrating salmon, which leave a quantitative signature on the makeup of plant communities near spawning streams. Thus, nutrient‐mediated habitat filtering could be reduced by salmon nutrients. Here, we ask how salmon abundance affects the phylogenetic structure of riparian flowering plant assemblages across 50 watersheds in the Great Bear Rainforest of British Columbia, Canada. Based on a regional pool of 60 plant species, we found that assemblages become more phylogenetically dispersed and species poor adjacent to streams with higher salmon spawning density. In contrast, increased phylogenetic clumping and species richness was seen in sites with low salmon density, with steeper slopes, further from the stream edge, and within smaller watersheds. These observations are all consistent with abiotic habitat filtering and biotic competitive exclusion acting together across local and landscape‐scale gradients in nutrient availability to structure assembly of riparian flowering plants. In this case, rich salmon nutrients appear to release riparian flowering‐plant assemblages from the confines of a low‐nutrient habitat filter that drives phylogenetic clustering.

Detecting the threshold between ornamental landscapes and functional ecological communities: soil microarthropods as indicator species - Valentin Schaefer; Morgan Hocking (Urban Ecosystems, 2015)